PENERAPAN WAKTU PADA PROYEK PEMBANGUNAN GEDUNG ISOLASI RSUD MEURAXA KOTA BANDA ACEH MENGGUNAKAN METODE CRITICAL PATH METHOD (CPM) - Muhammad Jauhar Izzaki; Muhammad Ridha; Amalia Effendy (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
This research was conducted using the Critical Path Method (CPM) with the help of software in the form of Microsoft Excel and Microsoft Project. The purpose of this study was to determine the critical path and the non-critical path and to determine the duration of the project after being calculated using the Critical Path Method (CPM) in the construction work of the isolation room at Meuraxa Hospital, Banda Aceh City. Therefore, in this study, the authors conducted a study of project scheduling data for the Isolation Building Construction of the Meuraxa Hospital in Banda Aceh City, where the overall scheduling used the Gantt Chart method. In this study, only RAB and S-curve data were needed. The results of the analysis using the Critical Path Method (CPM) method obtained a total duration of 151 days from the initial total duration of 161 days of work activities. The difference in decreasing day duration is 10 days or 0.94%. And found 23 jobs on the critical path from a total of 42 jobs. The total initial wage cost with a normal duration of 161 days is IDR 728,332,768.20 while the total cost with a duration after using the Critical Path Method (CPM) method is obtained 151 days with a total employee wage cost of IDR 683,094,708.06. Then there is a wage efficiency of 6.21% or Rp. 45,238,060.14 of the total cost of workers' wages of Rp. 728,332,768.20. In implementing a project, it is necessary to plan activities carefully to avoid delays in carrying out the project.